PENERAPAN HUKUM SURAT EDARAN MAHKAMAH AGUNG NOMOR 3 TAHUN 2015 TERHADAP PENGGUNAAN NARKOBA UNTUK DIRI SENDIRI - Siagian, Ahmad Rifa’i (Jurnal Sostekmas: Jurnal Sosial, Teknologi, dan Pengabdian Masyarakat, 2026)
Drug abusers who are dependent will certainly continue to seek narcotics to meet their narcotic needs, even though they are expensive and prohibited by law. Supreme Court Circular Letter Number 3 of 2015 indicates that judges who wish to use the Circular Letter must be able to "make sufficient considerations." The research method used is normative legal research. The results of the study indicate that the Judge's considerations in his decision when applying Supreme Court Circular Letter Number 3 of 2015 are the facts revealed during the trial, although the Judge's examination and decision must be based on the Public Prosecutor's indictment (Article 182 paragraphs 2 and 3 of the Criminal Procedure Code). The Prosecutor charged with Article 111 or Article 112 of Law Number 35 of 2009 concerning narcotics, but based on the legal facts revealed during the trial, Article 127 of Law Number 35 of 2009 concerning narcotics was proven, an article which was not indicted. The Defendant was a relatively small user.